LCIA framework and cross-cutting issues guidance within the UNEP-SETAC Life Cycle Initiative - Verones, Francesca; Bare, Jane; Bulle, Cécile; Frischknecht, Rolf; Hauschild, Michael; Hellweg, Stefanie; Henderson, Andrew; Jolliet, Olivier; Laurent, Alexis; Liao, Xun; Lindner, Jan Paul; Maia de Souza, Danielle; et al. (Journal of cleaner production, 2017)
Increasing needs for decision support and advances in scientific knowledge within life cycle assessment (LCA) led to substantial efforts to provide global guidance on environmental life cycle impact assessment (LCIA) indicators under the auspices of the UNEP-SETAC Life Cycle Initiative. As part of these efforts, a dedicated task force focused on addressing several LCIA cross-cutting issues as aspects spanning several impact categories, including spatiotemporal aspects, reference states, normalization and weighting, and uncertainty assessment. Here, findings of the cross-cutting issues task force are presented along with an update of the existing UNEP-SETAC LCIA emission-to-damage framework. Specific recommendations are provided with respect to metrics for human health (Disability Adjusted Life Years, DALY) and ecosystem quality (Potentially Disappeared Fraction of species, PDF). Additionally, we stress the importance of transparent reporting of characterization models, reference states, and assumptions, in order to facilitate cross-comparison between chosen methods and indicators. We recommend developing spatially regionalized characterization models, whenever the nature of impacts shows spatial variability and related spatial data are available. Standard formats should be used for reporting spatially differentiated models, and choices regarding spatiotemporal scales should be clearly communicated. For normalization, we recommend using external normalization references. Over the next two years, the task force will continue its effort with a focus on providing guidance for LCA practitioners on how to use the UNEP-SETAC LCIA framework as well as for method developers on how to consistently extend and further improve this framework. •The existing UNEP-SETAC LCIA framework was updated.•Recommendations were formulated for several LCIA cross-cutting issues.•Recommendations were provided for specific areas of protection.•Continuous efforts will focus on further harmonizing cross-cutting issues in LCIA.